Integration of Environmental Concern Values in the National Legal System as an Effort to Strengthen Ecological Citizenship through the Role of FDLH in Balikpapan City - Tammu, Herlindar; Suryaningsi, Suryaningsi; Jamil, M; Majid, Novita (Dinasti Research, 2025)
The integration of environmental concern values into the national legal system is a strategic step in fostering ecological awareness and responsibility among citizens. This study examines how these values are implemented through Law No. 32 of 2009 on Environmental Protection and Management, alongside the active role of the Regional Environmental Forum (FDLH) in Balikpapan City in strengthening ecological citizenship. A qualitative case study approach was employed to explore FDLH's contributions in educating the public, encouraging civic participation, and advocating sustainable environmental policies. The findings reveal that FDLH plays a crucial role as a bridge between society, government, and businesses in promoting environmental concern values embedded in national law. However, challenges remain in law enforcement and public participation, which require enhanced institutional capacity and more systematic environmental education. This study offers strategic recommendations to improve the effectiveness of integrating environmental values in both legal frameworks and social practices, aiming to realize sustainable ecological citizenship at the local level.